MURABAHAH PROVISION: THE KEY TO CLIENT-ORIENTED BUSINESS STRATEGIES AT BMT EL-MUHSIN - Mardianton, Mardianton; Efendi, Faisal; Hertasmaldi, Hertasmaldi; Mulyani, Ridha; Nurlaila, Nurlaila (J-ISCAN: Journal of Islamic Accounting Research, 2024)
The research objective of this paper is to examine the impact of murabahah financing and entrepreneurial spirit on the income of Baitul Mal wa Tamwil El-Muhsin customers. This quantitative study comprises two independent variables and one dependent variable. There are 1,085 customers in the population. The Cochran formula was employed to implement stratified random sampling. A total of 196 customers were chosen as samples. The data collection technique employs a questionnaire, while the data analysis technique on the impact of financing and entrepreneurial spirit on customer income employs path analysis. The F test results indicated that the entrepreneurs of BMT el-Muhsin Hall have a substantial impact on their souls, with a F count of 17,664. Despite the fact that the coefficient of the financing route has a significant partial influence on the soul of entrepreneurs at BMT el-muhsin Hall (T count = 4,203), the hypothesis is acceptable. Structural analysis 2 demonstrated that the revenue of BMT el-Muhsin Hall customers was significantly impacted by the financing of mortgages and the spirit of entrepreneurship, with a value of 73.10%. Although the analysis of the murabahah financing route has a partial influence of 69.00% on the soul of entrepreneurs and the coefficient of the spirit of enterprises has a significant influence on the income of the entrepreneur of 11.30%, thus, the hypothesis is accepted.